2021
DOI: 10.4018/jgim.289651
|View full text |Cite
|
Sign up to set email alerts
|

Does the Kyoto Protocol as an International Environmental Policy Promote Forest Carbon Sinks?

Abstract: Under the background of carbon neutrality, the carbon sequestration of forest ecosystems is an important way to mitigate climate change. Forest could not only protect the environment but also an important industry for economic development. As an international climate policy that first recognized the role of forest carbon sinks on climate change, the question becomes, has the Kyoto Protocol promoted the development of forest carbon sinks in contracting parties? To explore this, data of forest can be obtained a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 45 publications
1
6
0
Order By: Relevance
“…The forest area proportion, wood harvest volume, and forest management behavior had positive and significant effects on forest carbon storage. The above conclusions are consistent with many studies [ 18 , 34 , 40 , 52 ]. This result, that the amount of wood harvested has a positive effect on forest carbon storage, is somewhat counterintuitive.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…The forest area proportion, wood harvest volume, and forest management behavior had positive and significant effects on forest carbon storage. The above conclusions are consistent with many studies [ 18 , 34 , 40 , 52 ]. This result, that the amount of wood harvested has a positive effect on forest carbon storage, is somewhat counterintuitive.…”
Section: Resultssupporting
confidence: 93%
“…Examining the influence of forest carbon sinks requires not only considering the driving role of natural factors but also the impact of policy initiatives, such as climate policy, on forest carbon sinks [ 39 ]. At the international level, Ge and Lin used a synthetic control method for analysis and found that the Kyoto Protocol had a significant promoting effect on the development of forest carbon sinks in signatory countries [ 40 ]. At the national and local government levels, climate policy has gradually shifted from single-sectoral to cross-sectoral policies [ 41 ].…”
Section: Literature Review and Research Hypothesismentioning
confidence: 99%
“…Following the approach of the current literature [3][4][5], the following variables are controlled in the baseline model: logarithm of per capita GDP (GDPP); agricultural value added (AGRI ); industrial value added (I NDU); service industry value added (SERV); and urbanization rate (URBA), represented by the proportion of urban population at the end of the year. The GDP growth rate (GDPG) and population growth rate (POPG) are measured as Equations ( 2) and (3), respectively.…”
Section: Control Variablesmentioning
confidence: 99%
“…For example, some scholars have quantitatively identified the relationship between institutional freedom and FCS growth [3,4]. Ge and Lin [5] examined the relationship between the signing of the Kyoto Protocol and FCS. Zhao et al [6] compared the interregional spillover effects of FCS in China from the perspectives of the natural environment, economic development, forest management, and environmental regulation.…”
Section: Introductionmentioning
confidence: 99%
“…The forest carbon sink is a process through which forest ecosystems absorb and sequester carbon dioxide, making it a crucial factor in reducing atmospheric carbon dioxide concentrations [1,2]. As the largest carbon pool in terrestrial ecosystems, forest plays an vital role in promoting economic and social development and environmental protection [3,4]. According to the inventory data of seven forest resources in China from 1977 to 2013, the raw carbon storage of China's forests has increased by 72.62%, reaching 7.27 Pg C, of which the carbon storage of natural forests accounts for about 85%, and is expected to continue to increase in the future [5].…”
Section: Introductionmentioning
confidence: 99%